2009
DOI: 10.1080/15374410903401153
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Conflict and Violence Across Contexts: Relations to Adjustment Among Palestinian Children

Abstract: Despite extensive literatures on the impact on children of exposure to violence in families, neighborhoods, and peer groups, there has been relatively little effort evaluating their cumulative impact. There also has been less attention to the effects of exposure to political conflict and violence. We collected data from a representative sample of 600 Palestinian youths (three age cohorts: 8, 11, and 14 years old) to evaluate the relation of exposure to political conflict and violence, and violence in the famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 67 publications
9
114
0
Order By: Relevance
“…The protective effect of a positive supportive family environment replicates what the authors previously found in two other independent war-exposed samples studied after the 1996 war in Lebanon [17,31], as well as reports by other researchers [18][19][20][21]32]. This raises the need to implement interventions during peace time as well as at the onset of war events to alert parents and raise their awareness about the importance of family-together time, supervision of school work, using non-violent means of communication and discipline as well as avoidance of television time in favor of promotion of hobbies and other leisure activities.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The protective effect of a positive supportive family environment replicates what the authors previously found in two other independent war-exposed samples studied after the 1996 war in Lebanon [17,31], as well as reports by other researchers [18][19][20][21]32]. This raises the need to implement interventions during peace time as well as at the onset of war events to alert parents and raise their awareness about the importance of family-together time, supervision of school work, using non-violent means of communication and discipline as well as avoidance of television time in favor of promotion of hobbies and other leisure activities.…”
Section: Discussionsupporting
confidence: 87%
“…Children experiencing family violence during war were more likely to have PTSD [17][18][19][20], as well as attentional and oppositional behavioral problems [21]. Mothers with highly punitive discipline styles were more likely to have adolescents with lower scores on Resilience [22].…”
mentioning
confidence: 95%
“…Three studies found non-significant findings between sex and PTSD symptom severity (PunamĂ€ki et al, 2001; Qouta et al, 2007; Thabet et al, 2009). One study examined the association of age and PTSD and concluded that those who are older were more likely to experience PTSD symptoms (Dubow et al, 2009). Three studies found non-significant findings between age and PTSD symptoms (Khamis, 2005, 2008; PunamĂ€ki et al, 2001; Thabet et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…There is ample evidence of war trauma negatively affecting children’s mental health by increasing symptoms of PTSD, depression, anxiety, and aggression (Attanayake et al, 2009; Dubow et al, 2009). Less is known about war trauma’s impacts on children’s attachment styles, although, theoretically, trauma is assumed to increase the risk of insecure attachment.…”
Section: Introductionmentioning
confidence: 99%